Internal Facilitation by Health Assistants for the “WHO Lay Health Worker Dementia Care” in Rural Uganda: A Formative Evaluation - Edith K Wakida; Celestino Obua; Godfrey Zari Rukundo; Mary Samantha; Samuel Maling; Christine K Karungi; Zohray M Talib; Jessica Haberer; Stephen J Bartels (Journal of Multidisciplinary Healthcare, 2025)
Background: Dementia is characterized by cognitive symptoms like memory loss, difficulty with language, and impaired judgment, alongside behavioral and psychological symptoms such as depression, anxiety, and aggression. Early diagnosis and tailored care are essential for managing these symptoms, improving quality of life, and reducing caregiver burden. Dementia affects a substantial portion of older people globally, especially in low- and middle-income countries like Uganda, where rural healthcare systems face challenges in dementia care access. To address these needs, we gathered key stakeholders’ perspectives on a culturally tailored model employing lay health workers, supported by health assistants as internal facilitators, to implement the World Health Organization dementia toolkit in rural communities. Methods: We conducted a formative qualitative study, utilizing one-on-one interviews with health assistants, district health team members, and primary healthcare providers in rural Uganda. We solicited their perspectives on implementing the World Health Organization dementia toolkit at the village level. The integrated Promoting Action on Research Implementation in Health Services (i-PARIHS) framework guided data collection and analysis, focusing on implementation support, process improvement, and practice sustainment. Results: Strong support was found for health assistants’ roles in facilitating lay health worker-led dementia care at the community level. Health assistants’ familiarity with lay health workers and pre-established structures were considered facilitating factors. Key challenges included knowledge gaps in dementia care and limited resources. Participants emphasized the importance of training, mentorship, and standardized reporting tools to enhance the implementation of dementia care. They recommended providing the health assistants with job guides, updated reporting templates to collect dementia indicators, and orientation on what they should do during internal facilitation with the lay health workers using the dementia toolkit. Conclusion: Health assistants’ internal facilitation provides a promising strategy for scaling dementia care in rural Uganda by leveraging community-based lay health workers. Addressing identified knowledge gaps, communication needs, and resource constraints will be essential to sustaining dementia care interventions in these communities.
Keywords: Dementia care; Internal facilitation; Lay health workers; Uganda; Rural health; i-PARIHS framework